English vocabulary word games and pictures : for elementary level. book 1 (Deepublish, 2017)
This book aims at helping English teachers to teach their students in a fun way as well as facilitating English learners to learn in an enjoyable way. It has particularly designed to teach and learn vocabulary for elementary level, thus, the level of difficulty suits best leaners ability. Pictures are provided throughout the book to help the learners understand the lessons well. It's important to note that all pictures used in this book are not